A CagA‐independent cluster of antigens related to the risk of noncardia gastric cancer: Associations between Helicobacter pylori antibodies and gastric adenocarcinoma explored by multiplex serology. Issue 12 (3rd December 2013) - Song, Huan; Michel, Angelika; Nyrén, Olof; Ekström, Anna‐Mia; Pawlita, Michael; Ye, Weimin
<x xml:space="preserve">Abstract</x> Because of the differences in bacterial epitopes and host characteristics, infections with Helicobacter pylori (H. pylori) induce different immune responses. We explored the possibility that certain antibody response patterns are more closely linked to gastric adenocarcinoma (GAC) than others. In a Swedish population‐based case‐control study, serum samples were obtained from 268 cases and 222 controls, aged 40–79 years and frequency‐matched according to age and sex. We measured antibodies against 17 H. pylori proteins using multiplex serology. Associations were estimated with multivariably adjusted logistic regression models, using odds ratio (OR) with 95% confidence interval (CI) as measures of relative risk. Associations were essentially confined to non‐cardia GAC but did not differ significantly between intestinal and diffuse subtypes. Point estimates for all antibodies were above unity, 15 significant with top three being CagA (OR = 9.2), GroEL (6.6), HyuA (3.6). ORs were substantially attenuated in individuals with chronic atrophic gastritis. Principal component analysis identified two significant factors: a CagA‐dominant factor (antibodies against CagA, VacA and Omp as prominent markers), and a non‐CagA factor (antibodies against NapA and Catalase as prominent markers). Both factors showed dose‐dependent associations with non‐cardia GAC risk (CagA‐dominant factor, highest vs. lowest quartiles, OR = 16.2 [95% CI 4.8–54.9]; non‐CagA factor OR = 5.3 [95% CI 2.1–13.3]). Overall, our results confirm that serum antibodies against different H. pylori proteins are associated with the presence of non‐cardia GAC. Although strongest association is detected by antibodies against CagA and covarying proteins, a pattern of antibodies unrelated to CagA is also significantly linked to the risk of non‐cardia GAC.